2014
DOI: 10.1007/s00403-014-1438-x
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 participates in human skin keloid formation by inhibiting fibroblast proliferation

Abstract: Abnormal scarring results from the expression and composition of extracellular matrix molecules. The transcription and translation of collagens I and III, fibronectin, laminin, periostin, and tenascin are all increased in raised dermal scar tissue. However, human keloid development is not fully defined. In this study, we identified proteins expressed differentially between normal skin and keloid scar tissues and examined their function in keloid formation using fibroblasts. Skin specimens from normal volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Type V collagen is particularly abundant in vascular tissues and contributes to binding to other connective tissue cells . This collagen type was detected as upregulated in human skin keloid formation . The major function of collagen VI is probably as an anchoring meshwork connecting collagen fibers to the surrounding matrix, but the precise role of collagen VI in cartilage has not been clearly defined .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type V collagen is particularly abundant in vascular tissues and contributes to binding to other connective tissue cells . This collagen type was detected as upregulated in human skin keloid formation . The major function of collagen VI is probably as an anchoring meshwork connecting collagen fibers to the surrounding matrix, but the precise role of collagen VI in cartilage has not been clearly defined .…”
Section: Discussionmentioning
confidence: 99%
“…23 This collagen type was detected as upregulated in human skin keloid formation. 24 The major function of collagen VI is probably as an anchoring meshwork connecting collagen fibers to the surrounding matrix, but the precise role of collagen VI in cartilage has not been clearly defined. 25 Veidal et al suggested that collagen VI turnover is a central player in liver fibrogenesis.…”
Section: Collagen IIImentioning
confidence: 99%
“…Overexpression of extracellular matrix protein 1 could regulate angiogenesis . Studies have also found that the expression of extracellular matrix molecules is associated with scar formation, and the levels of annexin A2 and serum albumin precursors in keloids are downregulated compared to those in normal skin …”
Section: Discussionmentioning
confidence: 99%
“…47 Studies have also found that the expression of extracellular matrix molecules is associated with scar formation, and the levels of annexin A2 and serum albumin precursors in keloids are downregulated compared to those in normal skin. 48 Dermcidin was first discovered in the sweat glands of human skin and has broad-spectrum antimicrobial effects 49 ; this protein is found in the sweat glands of human skin as part of the innate immune defense system. It has been demonstrated that dermcidin concentrations in the sweat of patients infected with trichophyton are lower than those healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression of annexin A2 was observed, this protein functions in regulating fibroblast proliferation and migration. It is hypothesized that Annexin A2 is involved in skin keloid formation and may be a potential target for therapeutic interventions of keloid lesions (51).…”
Section: Lfq Intensities (Medians)mentioning
confidence: 99%